Measuring the cost-effectiveness of treatments for people with multiple sclerosis: Beyond quality-adjusted life-years. (March 2022) - Hawton, Annie; Goodwin, Elizabeth; Boddy, Kate; Freeman, Jennifer; Thomas, Sarah; Chataway, Jeremy; Green, Colin
Background: It is a familiar story. A promising multiple sclerosis (MS) treatment clears the three regulatory hurdles of safety, quality and efficacy, only to fall at the fourth: cost-effectiveness. This has led to concerns about the validity of the measures typically used to quantify treatment effects in cost-effectiveness analyses and in 2012, in the United Kingdom, the National Institute for Health and Care Excellence called for an improvement in the cost-effectiveness framework for assessing MS treatments. Objective and Methods: This review describes what is meant by cost-effectiveness in health/social care funding decision-making, and usual practice for assessing treatment benefits. Results: We detail the use of the quality-adjusted life-year (QALY) in resource allocation decisions, and set out limitations of this approach in the context of MS. Conclusion: We conclude by highlighting methodological and policy developments which should aid addressing these limitations.